Quantitative analyses of multidimensional ecological impacts of Talatan photovoltaic power plant on desert ecosystems in Northwestern China - Yishuang Tong; Qian Ding; Chongbin Xu; Qian Chen; Guojin He; Zhiyun Ouyang; Wu Yang (Environmental Research Letters)
Globally, solar energy has supplanted fossil fuels as the predominant source of clean energy. Scholars have been calling for techno-ecological synergies that minimizing unintended environmental consequences; however, empirical evidence is largely missing in the existing literature. Taking the world’s largest photovoltaic (PV) power plant as a demonstration, combining remote sensing images with field data, we actively used the spatiotemporal dynamic analysis, gross ecosystem products accounting method and statistical analysis methods to show techno-ecological synergies for electricity generation and ecological recovery. Specifically, our analyses reveal that (1) PV panels reduced surface albedo. The albedo of three broad spectral bands decreased by >15% in PV area; (2) comparing to areas between and outside the PV areas, areas under the PV panels enhanced vegetation cover by 61.86% (absolute coverage of 38.22%) and 131.80% (absolute coverage of 56.86%), unit area above-ground biomass by 133.71% (119 g) and 235.48% (146 g), and plant height by 31.02% (17.36 cm) and 45.58% (22.96 cm), respectively. Nevertheless, PV panels exerted a negative impact on soil organic matter but did not significantly affect other soil and vegetation indicators (i.e. soil water content, vegetation nitrogen content, and vegetation biodiversity, etc); and (3) PV panels improved ecosystem services. Specifically, from 2010 to 2020, among the four ecosystem regulating services, carbon sequestration and oxygen release increased by 178.46% (70.92 t km ^−2 and 51.58 t km ^−2 ), sand fixation by 13.76% (3920.19 t km ^−2 ), and soil retention by 4.16% (467.02 t km ^−2 ), respectively. Our study demonstrates a potentially sustainable mode in desert areas that supports vertical multiple land uses, improves the surface ecological environment while harnesses solar energy. With better understanding and management of the coupled human-natural energy systems, including the light allocation between PV panels, the selection of appropriate vegetation types beneath panels, and effective management, it is promising that there will be more techno-ecological synergies worldwide.